ROLE OF ALUMNI IN THE PROGRAM MENTORSHIP TO SUPPORT INTERNATIONAL ACHIEVEMENTS: Phenomenological Study At Mts Abadiyah Pati - Kalim, Abdul; Islah, Islah; Sujito, Sujito (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This study aims to examine the role of alumni in the mentorship program to support the international achievements of MTs Abadiyah Pati students. Specifically, exploring the dynamics of alumni involvement in assisting madrasah students to compete at the global level, as well as identifying key factors that influence the effectiveness of the mentorship program in the context of Islamic education. The method used is a qualitative approach with a phenomenological design. Data collection was carried out through in-depth interviews, participant observation, and analysis of program documents during the period 2018-2023. The study involved 12 key informants consisting of alumni mentors, international high-achieving students, and mentorship program managers. Data were analyzed using thematic analysis techniques to identify patterns of alumni roles and their impacts. The results of the study revealed that alumni play three main roles in the mentorship program: (1) inspiring role models who break stereotypes about the limitations of madrasa graduates, (2) academic mentors who facilitate the transfer of knowledge and competition strategies, (3) a central role as international network facilitators who open access to global resources, psychological-emotional supporters who understand the specific pressures and challenges of madrasa students. These findings indicate that the alumni mentorship program plays a significant role in improving student achievement in international competitions in science, technology, and arts and culture. Further research recommendations require a study of the impact of the mentorship program on academic and professional journeys to expand the reach and positive impact of alumni on madrasa students throughout Indonesia.